(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2014)
Empathy is inseparable from social and cultural. One district in Surakarta Cities, Central Java that still has a specific character is Baluwerti which is the area for family and courtiers of Kasunanan palace. The problem of the development in Baluwerti Settlement is as a result the shift of empathy from its inhabitants. To assess, used syncrhonic-diachronic reading methods. Assessment of physical aspects reviewed through of compliance with spatial concepts of Mataram (Java) state. Assessment of non-physical aspects include: the function of the building, socio-cultural, and ownership status. It is known that a shift in physical and non-physical aspects are the impact from reduced of the occupants empathy towards the Baluwerti existence.